2023
DOI: 10.1002/asia.202201269
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Synthesis of Bisphosphinated Quinoxalines via Radical Cyclization ofo‐Diisocyanoarenes with Diphosphines

Abstract: The cycloaddition reaction of o-diisocyanoarenes with interelement compounds under light is a very important reaction system to clarify whether this reaction proceeds by radical cyclization or by aza-Bergman cyclization. In this study, a series of diphosphines with phosphorus-phosphorus single bonds were selected as interelement compounds, and their cycloaddition reactions with o-diisocyanoarenes under light were investigated in detail to achieve a novel photo-induced synthesis of bisphosphinated quinoxalines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…62 Scheme 22 Phosphinylation of unactivated ethers 61 Recently, Ogawa and Yamamoto reported the photoinduced synthesis of bisphosphinated quinoxalines through reactions between o-diisocyanoarenes and diphosphines, all without the need for any photocatalyst. 63 A thorough mechanistic study suggested a process involving radicalmediated cyclization.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…62 Scheme 22 Phosphinylation of unactivated ethers 61 Recently, Ogawa and Yamamoto reported the photoinduced synthesis of bisphosphinated quinoxalines through reactions between o-diisocyanoarenes and diphosphines, all without the need for any photocatalyst. 63 A thorough mechanistic study suggested a process involving radicalmediated cyclization.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…[20] Based on this background, we have energetically developed straightforward synthetic methods of phosphorus-heteroatom compounds and their application to the functionalization of carbon-carbon unsaturated compounds via radical reactions and transition-metal-catalyzed reactions. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In particular, we have found that diphosphines containing phosphorusphosphorus single bonds can efficiently react with organic dichalcogenides to form the corresponding phosphorus-chalcogen interelement compounds. [32] Among a variety of diphosphines, tetraphenyldiphosphine disulfide, Ph 2 P(S)-P(S)Ph 2 1, is quite stable to air and moisture.…”
Section: Introductionmentioning
confidence: 99%
“…This is because strict degassing and dehydration techniques for treatment of air- and moisture-sensitive organophosphorus compounds were insufficient at that time. After that, we have developed a series of addition reactions of phosphorus compounds, especially diphosphine analogues, to unsaturated bonds and have accumulated expertise in the handling of organophosphorus compounds …”
Section: Introductionmentioning
confidence: 99%